The phenuivirus Toscana virus makes an atypical use of vacuolar acidity to enter host cells - Koch, Jana; Xin, Qilin; Obr, Martin; Schäfer, Alicia; Rolfs, Nina; Anagho, Holda A.; Kudulyte, Aiste; Woltereck, Lea; Kummer, Susann; Campos, Joaquín; Uckeley, Zina Maria; Bell-Sakyi, Lesley; et al. (PLoS pathogens, 2023)
Toscana virus is a major cause of arboviral disease in humans in the Mediterranean basin during summer. However, early virus-host cell interactions and entry mechanisms remain poorly characterized. Investigating iPSC-derived human neurons and cell lines, we found that virus binding to the cell surface was specific, and 50% of bound virions were endocytosed within 10 min. Virions entered Rab5a+ early endosomes and, subsequently, Rab7a+ and LAMP-1+ late endosomal compartments. Penetration required intact late endosomes and occurred within 30 min following internalization. Virus entry relied on vacuolar acidification, with an optimal pH for viral membrane fusion at pH 5.5. The pH threshold increased to 5.8 with longer pre-exposure of virions to the slightly acidic pH in early endosomes. Strikingly, the particles remained infectious after entering late endosomes with a pH below the fusion threshold. Overall, our study establishes Toscana virus as a late-penetrating virus and reveals an atypical use of vacuolar acidity by this virus to enter host cells.
Gesehen am 11.06.2024